Massive Bleeding After Surgical Repair in Acute Type A Aortic Dissection Patients: Risk Factors, Outcomes, and the Predicting Model - Zhang, Chen-Han; Ge, Yi-Peng; Zhong, Yong-Liang; Hu, Hai-Ou; Qiao, Zhi-Yu; Li, Cheng-Nan; Zhu, Jun-Ming (Frontiers in Cardiovascular Medicine, 2022)
Background: Massive bleeding throughout aortic repair in acute type A dissection (ATAAD) patients is a common but severe condition that can cause multiple serious clinical problems. Here, we report our findings regarding risk factors, short-term outcomes, and predicting model for massive bleeding in ATAAD patients who underwent emergent aortic repair. Methods: A universal definition of perioperative bleeding (UDPB) class 3 and 4 were used to define massive bleeding and comprehensively evaluate patients. A total of 402 consecutive patients were enrolled in this retrospective study during 2019. Surgical strategies used to perform aortic arch procedures included total arch and hemiarch replacements. In each criterion, patients with massive bleeding were compared with remaining patients. Multivariable regression analyses were used to identify independent risk factors for massive bleeding. Logistic regression was used to build the model, and the model was evaluated with its discrimination and calibration. Results: Independent risk factors for massive bleeding included male sex (OR=6.493, P<0.001), elder patients (OR=1.029, P=0.05), low BMI (OR=0.879, P=0.003), emergent surgery (OR=3.112, P=0.016), prolonged cardiopulmonary bypass time (OR=1.012, P=0.002), lower hemoglobin levels (OR=0.976, P=0.002), increased D-dimer levels (OR=1.000, P=0.037), increased fibrin degradation products (OR=1.019, P=0.008), hemiarch replacement (OR=5.045, P=0.037), total arch replacement (OR=14.405, P=0.004). The early-stage mortality was higher in massive bleeding group (15.9% vs 3.9%, P=0.001). The predicting model showed a well discrimination (AUC=0.817) and calibration (χ2=5.281, P=0.727>0.05). Conclusions: Massive bleeding in ATAAD patients who underwent emergent aortic repair is highly associated with gender, emergent surgery, increased D-dimer levels, longer CPB time, anemia, and use of a complex surgical strategy. Since massive bleeding may lead to worse outcomes, surgeons should choose suitable surgical strategies in patients who are at a high risk of massive bleeding.